Phage biocontrol of enteropathogenic and shiga toxin-producing Escherichia coli in meat products - Tomat, David D.; Migliore, Leonel; Aquili, Virginia; Quiberoni, Andrea del Luján; Balague, Claudia (Frontiers in Cellular and Infection Microbiology, 2013)
Ten bacteriophages were isolated from faeces and their lytic effects assayed on 103 pathogenic and non-pathogenic Enterobacteriaceae. Two phages (DT1 and DT6) were selected based on their host ranges, and their lytic effects on pathogenic E. coli strains inoculated on pieces of beef were determined. We evaluated the reductions of viable cells of Escherichia coli O157:H7 and non-O157 Shiga toxigenic E. coli strains on meat after exposure to DT6 at 5 and 24°C for 3, 6, and 24 h and the effect of both phages against an enteropathogenic E. coli strain. Significant viable cell reductions, compared to controls without phages, at both temperatures were observed, with the greatest decrease taking place within the first hours of the assays. Reductions were also influenced by phage concentration, being the highest concentrations, 1.7 × 1010 plaque forming units per milliliter (PFU/mL) for DT1 and 1.4 × 1010 PFU/mL for DT6, the most effective. When enteropathogenic E. coli and Shiga toxigenic E. coli (O157:H7) strains were tested, we obtained viable cell reductions of 0.67 log (p = 0.01) and 0.77 log (p = 0.01) after 3 h incubation and 0.80 log (p = 0.01) and 1.15 log (p = 0.001) after 6 h. In contrast, all nonpathogenic E. coli strains as well as other enterobacteria tested were resistant. In addition, phage cocktail was evaluated on two strains and further reductions were observed. However, E. coli bacteriophage insensitive mutants (BIMs) emerged in meat assays. BIMs isolated from meat along with those isolated by using the secondary culture method were tested to evaluate resistance phenotype stability and reversion. They presented low emergence frequencies (6.5 × 10−7–1.8 × 10−6) and variable stability and reversion. Results indicate that isolated phages were stable on storage, negative for all the virulence factors assayed, presented lytic activity for different E. coli virotypes and could be useful in reducing Shiga toxigenic E. coli and enteropathogenic E. coli viable cells in meat products.